The SAMI–Fornax Dwarfs Survey I: sample, observations, and the specific stellar angular momentum of dwarf elliptical galaxies. Issue 2 (13th July 2020) - Scott, Nicholas; Eftekhari, F Sara; Peletier, Reynier F; Bryant, Julia J; Bland-Hawthorn, Joss; Capaccioli, Massimo; Croom, Scott M; Drinkwater, Michael; Falcón-Barroso, Jésus; Hilker, Michael; Iodice, Enrichetta; Lorente, Nuria F P; et al.
ABSTRACT: Dwarf ellipticals are the most common galaxy type in cluster environments; however, the challenges associated with their observation mean that their formation mechanisms are still poorly understood. To address this, we present deep integral field observations of a sample of 31 low-mass (10 7.5 < M⋆ < 10 9.5 M⊙ ) early-type galaxies in the Fornax cluster with the SAMI instrument. For 21 galaxies, our observations are sufficiently deep to construct spatially resolved maps of the stellar velocity and velocity dispersion – for the remaining galaxies, we extract global velocities and dispersions from aperture spectra only. From the kinematic maps, we measure the specific stellar angular momentum λ R of the lowest mass dE galaxies to date. Combining our observations with early-type galaxy data from the literature spanning a large range in stellar mass, we find that λ R decreases towards lower stellar mass, with a corresponding increase in the proportion of slowly rotating galaxies in this regime. The decrease of λ R with mass in our sample dE galaxies is consistent with a similar trend seen in somewhat more massive spiral galaxies from the CALIFA survey. This suggests that the degree of dynamical heating required to produce dEs from low-mass starforming progenitors may be relatively modest and consistent with a broad range of formation mechanisms.